The Legacy of COVID-19: Hospital Fear Led to the Delayed Diagnosis of an Ovarian Tumor with Massive Ascites and Extensive Abdominal Necrosis - Janos Szederjesi; Calin Molnar; Claudiu Molnar-Varlam; Dorin Dorobanțu; Mihai Claudiu Pui; Matild Keresztes (Life)
The COVID-19 pandemic has significantly impacted healthcare-seeking behaviors, leading to delayed cancer diagnoses due to hospital-related anxiety. This case highlights the severe consequences of delayed medical consultation in a patient with advanced ovarian cancer. A 47-year-old female presented with severe abdominal distension, massive ascites, and extensive abdominal wall necrosis after avoiding medical care for months due to severe hospital-related anxiety, exacerbated by the loss of her husband during the COVID-19 pandemic. On admission, a CT scan could not be performed due to the patient’s inability to lie supine and extreme abdominal distension. To relieve pressure and improve respiratory function, an abdominal drain was inserted, releasing 72 L of ascitic fluid over five days. Following drainage, imaging confirmed a large ovarian tumor with peritoneal involvement, and a multidisciplinary team (surgeons, gynecologists, plastic surgeons, anesthetists, and intensive care specialists) determined the need for surgical intervention. Histopathology confirmed mucinous adenocarcinoma with pseudomyxoma peritonei (FIGO IIIB). This case underscores the critical impact of delayed oncological diagnosis and the need for enhanced patient education, mental health support, and structured screening programs to prevent similar late-stage presentations.